Hydrochemical assessment of ground water quality at Kampong Jaya Gading - Mohammed Badraddin, Abdulmalek Khled (2018)
In Malaysia, groundwater is one of the sources of clean water, other than fresh river water and rain. Thus, this research had been done to determine the groundwater quality and also the effective type of well that can contribute to the good quality of groundwater. The parameters were considered such as PH, Electrical Conductivity, Turbidity, TDS, TSS, COD, BOD, manganese, iron, copper, zinc, lead, nitrate, total coliform and E.coli in this study. The water samples were collected from three different wells. The results were compared to the National Drinking Water Quality Standard (NDWQS) to know the class of the groundwater for each well. The result showed that the groundwater had been contaminated by the chromium with concentration of 1.59 mg/L which found in all wells. This result considered as relatively not in very high concentration even the concentration of element is higher than the standard stated by National Drinking Water Quality Standard (NDWOS). Meanwhile. for biological analysis result showed that total coliform and E.coli have highest contamination which was found in open wells with total coliform concentration 28 MPN/100 mL in opened well and 14 MPN/100 mL in closed well .E.coli concentration is 8.6 MPN/100 mL and 0MPN/100 mL in closed wells . As the conclusion, the groundwater quality was harmless from heavy metal concentration but highly contaminated with total coliform and E. coli. Quality of groundwater is equally important to its quantity owing to the suitability of water for various purposes.